2010
DOI: 10.1186/1471-2407-10-288
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS1 alters blood vessel morphology and TSP1 levels in LNCaP and LNCaP-19 prostate tumors

Abstract: Background: Decreased expression of the angiogenesis inhibitor ADAMTS1 (ADAM metallopeptidase with thrombospondin type 1 motif, 1) has previously been reported during prostate cancer progression. The aim of this study was to investigate the function of ADAMTS1 in prostate tumors.Methods: ADAMTS1 was downregulated by shRNA technology in the human prostate cancer cell line LNCaP (androgen-dependent), originally expressing ADAMTS1, and was upregulated by transfection in its subline , expressing low levels of ADAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
3
25
0
2
Order By: Relevance
“…As previous tumor studies have shown, the alteration of ADAMTS1 levels is accompanied by changes in the overall tumor structure and consistency, and specifically it has significant effects on the vasculature [4, 5, 2023]. Therefore we decided to explore the vascular pattern in our model.…”
Section: Resultsmentioning
confidence: 99%
“…As previous tumor studies have shown, the alteration of ADAMTS1 levels is accompanied by changes in the overall tumor structure and consistency, and specifically it has significant effects on the vasculature [4, 5, 2023]. Therefore we decided to explore the vascular pattern in our model.…”
Section: Resultsmentioning
confidence: 99%
“…46 VLDLR has been shown to be associated with obesity from both animal studies [47][48][49] and human GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…45 From animal studies, brahma gene expression is found to be restricted to mesodermal tissues involved in early vasculogenesis and heart morphogenesis. 46 VLDLR has been shown to be associated with obesity from both animal studies [47][48][49] and human GWAS. 50 Recently, a pathway analyses based on results from a GWAS has identified plausible biological links between VLDR with vascular endothelial growth factor, which is known to affect angiogenesis and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations